Experimental Investigation of the Effects of Reverse Bending and Straightening Process on Carbon Steel Bars used for Civil Engineering Applications - Adewole, K. K.; Bull, S. J. (Institute of Research and Community Outreach - Petra Christian University, 2014)
This paper presents an experimental investigation of the effects of reverse bending and straightening process on the mechanical properties of a typical carbon steel bar used for civil engineering applications. Twenty four specimens each were used for the metallogarphy, microhardness and tensile tests. The investigation revealed that the reverse bending and straightening process has no significant effect on the bars’ through-thickness microstructure and hardness. However, the reverse bending and straightening process reduces the yield load, ultimate load, and displacement at fracture of the bars by 4.27%, 2.58%, and 18.62% respectively. These results highlight the need to take into consideration the effects of the previous loading history of the bars/wires, particularly the reduction in the displacement at fracture and consequently, the ductility of the bars/wires in the design and fitness for purpose assessment of components made from them, since the bars/wires could experience high strain during installation and in service due to overloads.